Chemical sensitivity of Mo gate MOS capacitors - Lombardi, R. M. (2006)
Mo gate MOS capacitors exhibit a negative shift of their C-V characteristic by up to 240 mV, at 125°C, in response to 1000 ppm hydrogen, in controlled nitrogen atmospheres. The experimental methods for obtaining capacitance and conductance, as a function of polarisation voltage, as well as the relevant equivalent circuits are reviewed. The single-state interface state density, at the semiconductor-dielectric interface, decreases from 2.66 1011 cm-2e-v-1, in pure nitrogen, to 2.5 1011cm-2e-v-1 in 1000 ppm hydrogen in nitrogen mixtures, at this temperature.